Low grandparental social support combined with low parental socioeconomic status is closely associated with obesity in preschool‐aged children: a pilot study. Issue 4 (19th June 2015) - Lindberg, L.; Ek, A.; Nyman, J.; Marcus, C.; Ulijaszek, S.; Nowicka, P.
Summary: While the influence of parental socioeconomic status (SES) on children's weight status is well known, the impact of other family‐related aspects such as parental and grandparental social support is less understood. This study investigates the importance of parents' SES and social support (functional and structural) for weight status in a clinical sample of preschoolers 4–6 years old with obesity ( n = 39, 56% girls; 73% of parents were overweight/obese, 50% were of non‐Swedish origin). Linear regression analyses, simple and multiple, were performed on SES and social support with child BMI SDS (body mass index standard deviation score) as the dependent variable. The results show that parents' income and low emotional support from paternal grandparents were significantly associated with more severe obesity. The association between parental income and the child's BMI SDS was stronger among parents who had low emotional support from their own parents. In conclusion, grandparental social support may be protective against childhood obesity.